Analysis of Fundamental and Technical at PT Industri Jamu dan Farmasi Sido Muncul Tbk - Aqillah, Khayru; Daely, Riski Yunimanto; Muliyani (PT Katersi Minar Permata, 2025)
This study aims to analyze the correlation between a company's financial performance and stock price fluctuations in the capital market. Using a qualitative descriptive approach, this study applies fundamental analysis to annual financial reports and technical analysis through Relative Strength charts to identify price trends. The research focuses on PT Industri Jamu dan Farmasi Sido Muncul Tbk, utilizing secondary data sourced from the issuer's annual report and stock movement data from the Indonesia Stock Exchange (IDX). Research data confirms the consistent stability and resilience of PT Industri Jamu dan Farmasi Sido Muncul Tbk (SIDO)’s financial performance from 2019 to 2023, with fundamental indicators such as ROA, ROE, EPS, and PER showing positive trends and market adjustments. Despite the company's strong fundamentals, the stock price experiences fluctuations and a downward trend due to internal and external factors, including market conditions and investor sentiment. Technical analysis using indicators such as MACD and RSI helps identify short-term trading opportunities and market entry and exit timing. The combination of fundamental and technical analysis is crucial for assessing the potential and risks of investing in SIDO stock, as well as for more informed and responsive decision-making in response to market conditions.